Tribological behavior of TZ4YS-MoSi2 composites obtained by Spark Plasma Sintering. Issue 14 (November 2021) - Benavente, Rut; Salvador, María D.; Bloem, Carlos; Gutiérrez-González, Carlos F.; Alcázar, Carmen; Moreno, Rodrigo; Borrell, Amparo
Highlights: Increasing the percentage of MoSi2 in TZ4YS-MoSi2 composites leads to an improvement in their mechanical properties and is associated with a faster transition from light to severe wear due to the formation of the tribo-layer. Abstract: The aim of this work was to evaluate the role of MoSi2 content (5, 10, 15 wt%) in the mechanical and tribological behavior of TZ4YS-MoSi2 composites obtained by colloidal processing and spark plasma sintering (SPS) at 1500 °C. Firstly, the densification of TZ4YS-MoSi2 composite and the shrinkage-rate curves by SPS applying 80 MPa from 1300 °C to 1500 °C is studied. The hardness and fracture toughness values confirmed that up to 99.9% densification is gradually reached with increasing MoSi2 percentage. Secondly, pin-on-disk tribological tests at different distances (1, 5, 15 and 2000 m) with Al2 O3 as counterpart were performed to record the behavior of the materials in the initial and final stages of wear. The MoSi2 content was associated to the beginning of the transition from mild to severe wear, higher the amount of MoSi2 faster is the transition. This behavior was correlated with MoSi2 content, which aids the formation of a tribolayer.